Studi Kebijakan Pendidikan Agama Islam Pada Orde Lama, Orde Baru dan reformasi - Burhanudin Ata Gusman (SALIHA: Jurnal Pendidikan & Agama Islam, 2022)
Policies arise because there are problems that require action to address them properly. Education policy is the process of formulating reforms in actions that are easily accepted with common sense in solving educational problems. This study uses a literature study with qualitative methods. In collecting data using various sources from journals. The purpose of this study is to find out how education policy is in the old, new and reform eras. The results of the research show that during the New Order, the curriculum structure was valid from 1945 to 1950, namely the lowest education, teacher education, general education, vocational education, technical pedagogy, technical high school, higher education, republican higher education, higher education in the Dutch occupied areas. In the old order there was a curriculum from 1945 to 1968, lesson plans without problems in 1952, a 1964 curriculum, while in the new order the curriculum was 1967, 1975, 1984, 1994, while competency-based reforms, the 2006 and 2013 curriculum were needed. -policies contained in the old order until now, so that we know the history of education policies from the old order to the current reform.